2021
DOI: 10.1016/j.talanta.2020.121737
|View full text |Cite
|
Sign up to set email alerts
|

A multi-target lateral flow immunoassay enabling the specific and sensitive detection of total antibodies to SARS COV-2

Abstract: A rapid test for detecting total immunoglobulins directed towards the nucleocapsid protein (N) of severe acute syndrome coronavirus 2 (SARS CoV-2) was developed, based on a multi-target lateral flow immunoassay comprising two test lines. Both test lines bound to several classes of immunoglobulins (G, M, and A). Specific anti-SARS immunoglobulins were revealed by a colorimetric probe formed by N and gold nanoparticles. Targeting the total antibodies response to infection enabled achieving 100% diagnostic specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 28 publications
(43 reference statements)
1
56
0
Order By: Relevance
“…The nucleocapsid (N) antigen (1 mg/ml in phosphate buffer 20 mM pH 7.4) and staphylococcal protein A (SpA, 0.5 mg/ml in phosphate buffer) were spotted at 1 μl/cm by means of a XYZ3050 platform (Biodot, Irvine, CA, USA) to form the test (TL) and control (CL) lines, respectively. The preparation of the recombinant nucleocapsid protein was previously described in Cavalera et al (2020) and is detailed in the SI.
Fig.
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nucleocapsid (N) antigen (1 mg/ml in phosphate buffer 20 mM pH 7.4) and staphylococcal protein A (SpA, 0.5 mg/ml in phosphate buffer) were spotted at 1 μl/cm by means of a XYZ3050 platform (Biodot, Irvine, CA, USA) to form the test (TL) and control (CL) lines, respectively. The preparation of the recombinant nucleocapsid protein was previously described in Cavalera et al (2020) and is detailed in the SI.
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…For IgA analysis, we developed an LFIA based on a SARS-CoV-2-specific antigen (the nucleocapsid protein N), which is used as the capturing reagent and anchored onto the detection membrane. The N protein was selected among antigenic targets of the SARS coronavirus structure in a previous work of the group because it is highly immunogenic and abundantly expressed ( Zeng et al, 2020 ) and according to its reactivity to human sera from COVID-19 patients ( Cavalera et al, 2020 ) The optical immunosensor includes an anti-human IgA (anti-IgA) labelled with gold nanoparticles (GNP) to reveal the IgA bound to the N antigen. The anti-SARS-CoV-2 IgA in the serum/saliva sample is captured by the N antigen and stained by the GNP-labelled anti-IgA, forming a coloured band at the test line.…”
Section: Introductionmentioning
confidence: 99%
“…Point-of-care devices based on LFIA principle have been recently aimed at detecting the serologic response to the infection by specifically and separately targeting immunoglobulins belonging to the M and G classes in the blood serums [ 80 ]. The recent reports have shown that the multi-target LFIA can provide the specific and sensitive detection of total antibodies to SARS-COV-2 [ 81 ]. For instance, shown in Fig.…”
Section: Sars-cov-2 Detection Based On Applied Analytical Methodsmentioning
confidence: 99%
“…LFIAs can be used also to detect SARS-CoV-2 "total antibodies", as described by Cavalera and co-authors, who developed a POC multi-target LFIA enabling the specific and sensitive detection of total immunoglobulins (IgG, IgM, IgA) directed towards the N-protein of SARS-CoV-2 [122]. Specific anti-SARS-CoV-2 antibodies are revealed by a colorimetric probe formed by N-protein and gold NPs through a visual readout.…”
Section: Sars-cov-2 Antibody Detectionmentioning
confidence: 99%